Analysis of the Emergency Nursing Staff Need Using Baseline Emergency Staffing Tool (Best) In Indonesia: A Prospective Study - Putra, Kuswantoro Rusca; Rahmawati, Ike Nesdia; Noviyanti, Linda Wieke; Wulandari, Isti; Susilowati, Ratna (Universitas Airlangga, 2024)
Introduction: Patient density in the emergency room (ER) is a worldwide phenomenon and a major health-care issue. Because of the high degree of patient severity and the dynamic workflow, treating patients in the ER is frequently delayed. But, determining the need for nurses in the ER is difficult since patients arrive at random, including several complex situations, the quantity of patients, and the length of stay shifting greatly. This study aims to assess the emergency nursing staff need by determining the nurses' workload and patient dependency level in emergency room of the hospital using the baseline emergency staffing tool (BEST). Methods: A prospective observational research design was used in this study. A consecutive sample of 101 nurses selected in seven-day period in emergency department. The research was carried out in two government general hospitals situated in the provinces of Central Java and East Java. The BEST was used to estimate nursing staff requirement in emergency department and patient dependency was assessed using the Jones Dependency Tool (JDT). Results: Calculation of staff requirements in the ER of the first hospital has an average of 16 nurses, while the second hospital has an average of 30 people. The staffing challenges faced by these hospitals are significant, with a discrepancy of 3 nurses and 14 individuals in the ER. Based on the official hours, the highest number of staff needed in the evening and night while the relatively low number is in the morning. Conclusions: This gap in staffing might have an effect on how patient's outcomes and poses potential risks. To maintain the greatest standard of service, it is critical to account for changes in patient volume and alter staffing levels accordingly